Effect of acidification on the protection of alginate‐encapsulated probiotic based on emulsification/internal gelation. (18th March 2016) - Qu, Fangning; Zhao, Meng; Fang, Yapeng; Nishinari, Katsuyoshi; Phillips, Glyn O; Wu, Zhengjun; Chen, Chen
Abstract: BACKGROUND: The method of emulsification/internal gelation is commonly used to prepare alginate microspheres for lactic acid bacteria (LAB). This paper focused on the influence of acidification parameters, i.e. acid/Ca molar ratio and acidification time, on the physical properties and cell protection efficiency of microspheres and their correlations. RESULTS: With increasing acid/Ca molar ratio and acidification time, the average diameter of microspheres decreased and their mechanical strength increased. Interestingly, wet alginate microspheres shrank in simulated gastric juice (SGJ) while they swelled in bile salts solution (BS). The shrinkage or swelling ratio decreased with increasing mechanical strength. Correlation analysis showed that the encapsulated cell survivals in both SGJ and BS were positively correlated with the mechanical strength of microspheres but negatively with the shrinkage or swelling ratio. BacLight LIVE/DEAD assay suggested that the viability of encapsulated cells in fresh, SGJ‐treated and BS‐treated microspheres was closely related to cell membrane integrity. CONCLUSION: Acidification is a key step during microsphere preparation, which strongly affected the physical properties of alginate microspheres, resulting in different cell protection efficiency. The resulting well‐protected LAB can be applied in probiotics foods. © 2016 Society of Chemical Industry